2017
DOI: 10.3892/ol.2017.7071
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen 19‑9 as a prognostic biomarker in pancreatic neuroendocrine tumors

Abstract: Abstract. Carbohydrate antigen 19-9 (CA19-9) is not generally considered to be a biomarker in pancreatic neuroendocrine tumors (pNETs), as the majority of pNETs present with a normal range of CA19-9. The present study aimed to evaluate the role of serum CA19-9 levels as a prognostic factor in a relatively large number of patients with pNETs. Consecutive patients were retrospectively collected from a single institution between June 2006 and February 2015. The receiver operating characteristic (ROC) curve and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…30 CA19-9 is a tumor-associated antigen, which is a widely used marker for biliary and pancreatic cancer, initially reported by Koprowski et al 31 It has been reported as a prognostic biomarker for various tumors including GBC. [32][33][34] Although the optimal cutoff value is still controversial, the use of CA19-9 may provide an opportunity to guide personalized neoadjuvant therapy for GBC patients. 35 However, CA19-9 levels are elevated not only in the case of GBC but also in other cancers and certain inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…30 CA19-9 is a tumor-associated antigen, which is a widely used marker for biliary and pancreatic cancer, initially reported by Koprowski et al 31 It has been reported as a prognostic biomarker for various tumors including GBC. [32][33][34] Although the optimal cutoff value is still controversial, the use of CA19-9 may provide an opportunity to guide personalized neoadjuvant therapy for GBC patients. 35 However, CA19-9 levels are elevated not only in the case of GBC but also in other cancers and certain inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CA19-9 is a tumor-related carbohydrate biomarker, released from a human colorectal cancer cell line which is targeted by the monoclonal antibody 1116-NS-19-9. [ 23 ] The concentration of CA19-9 is correlated to the tumor mass, TNM stage, and recurrence. [ 3 ] However, it presents poor effectiveness in detecting in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CA199 can promote leukocyte aggregation by regulating leukocyte migration and adhesion in inflammatory regions[ 11 ]. As one of the common tumor markers, CA199 is mainly used in the auxiliary diagnosis and evaluation of disease progression and prognosis of pancreatic cancer, colorectal cancer, and other diseases[ 12 - 13 ]. In recent years, the abnormally elevated CA199 in some non-cancerous benign diseases has drawn increasing attention[ 14 - 16 ].…”
Section: Discussionmentioning
confidence: 99%